The girl in the mask - Jensen, Marie-Louise (Oxford University Press, 2012)
'Stand and Deliver! Hand over your valuables if you value your life!' Sophia's duty is clear. Look pretty, behave well, and find a husband as soon as possible. But Sophia hates the social whirl of balls and masquerades, so under the cover of darkness, she secretly swaps her ball gowns for breeches, and turns to highway robbery